The evolution of income inequality during the rise of the Swedish welfare state 1951 to 1973 - Anders Björklund; Mårten Palme (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
We analyse the change in family gross income inequality between 1951 and 1973. We use two new samples of the Swedish population from 1951 and 1956 containing tax register data, and compare the results with those obtained from the Swedish Level of Living survey from 1967 and 1973. Gini coefficients, four different Generalised entropy measures as well as decile group shares of total income are calculated. We also do two different decompositions: one between different demographic groups and one between the male and female component of family income. Finally, we examine to what extent zero family income records really reflect low economic welfare by using interview data from the 1968 Swedish Level of Living Survey.
Keywords: D30; I30; N30; 330; Income distribution; Household income; Einkommensverteilung; Sozialstaat; Schweden